2023
DOI: 10.31234/osf.io/xyrdt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The importance of face-shape masculinity for perceptions of male dominance depends on study design

Abstract: Dominance perceptions play an important role in social interactions. Although many researchers have proposed that masculine face-shape is an important cue for dominance perceptions, evidence for this claim has come almost exclusively from studies that assessed perceptions of experimentally manipulated face images using two-alternative forced-choice paradigms. Consequently, we investigated the role of masculine shape characteristics in perceptions of men’s facial dominance (1) using the two-alternative forced-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…For instance, when comparing the two-alternative forced-choice method to subjective ratings of attractiveness and objective measurements of facial shape characteristics, differences in outcomes have been observed (Jones & Jaeger, 2019; Lee et al, 2021; Scott et al, 2010). In a more recent study by Dong et al (2023), questions were raised about the predictive value of masculine shape characteristics and their role in determining dominance, as different perceptions of dominance were obtained based on the methodological approach used to assess shape-manipulated images.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, when comparing the two-alternative forced-choice method to subjective ratings of attractiveness and objective measurements of facial shape characteristics, differences in outcomes have been observed (Jones & Jaeger, 2019; Lee et al, 2021; Scott et al, 2010). In a more recent study by Dong et al (2023), questions were raised about the predictive value of masculine shape characteristics and their role in determining dominance, as different perceptions of dominance were obtained based on the methodological approach used to assess shape-manipulated images.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism of face shape was objectively measured for each of the 50 male and 50 female face images using the facefuns package (Holzleitner & DeBruine, 2021) in R (R Core Team, 2021), which implements shape analysis of images that have been delineated with standard landmarks. This method has been used in many previous studies to assess sexual dimorphism of face shape (e.g., Cai et al, 2019;Dong et al, 2023;Holzleitner et al, 2019;Leger et al, 2023;Komori et al, 2011). Shape components were first derived from Principal Component Analysis (PCA) of 132 Procrustes-aligned landmark points (see Holzleitner et al, 2019 for a diagram showing these facial landmarks) on each of the 50 male and 50 female face images.…”
Section: Sexual Dimorphism Of Face Shapementioning
confidence: 99%
“…However, several recent studies have reported that findings for social judgments of faces that were obtained using this method are often not observed (or, if observed, have considerably smaller effect sizes) in studies using natural face images and objective assessments of physical characteristics of faces (Dong et al, 2023;Jones & Jaeger, 2019;Jones et al, 2023;Lee et al, 2021;Leger et al, 2023;Scott et al, 2010). Given such results, many researchers have expressed concerns about the appropriateness of experimentally manipulated face images for studying social judgments of faces (Dong et al, 2023;Jones & Jaeger, 2019;Jones et al, 2023;Leger et al, 2023;Scott et al, 2010). Nonetheless, Boothroyd et al (2007) reported that experimentally manipulated masculinity did not influence the perceived health of male faces and also reported that masculinity and health ratings of natural male faces were not significantly correlated.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations